Fault Tolerance Impact on Near Field Communication for Data Storage of Mobile Commerce Technology in Cloud Computing - Noraziah, Ahmad; Herawan, Tutut; Ng, Liang Shen; Zailani, Abdullah; Balsam, A. Mustafa (2015)
Fault tolerance is a major concern to guarantee availability and reliability of critical services as well as application execution. Recently, due to rapid expansion of smart phone market and wireless communication environment, mobile devices are considered as resource for large scale distributed processing but there are several drawbacks, such as unstable wireless connection, limitation of data storage capacity,low communication bandwidth and frequent location changes. Cloud systems differ from these previous frameworks in that they are designed to support large numbers of customer-oriented applications, each with different quality of service (QoS) requirements and resource consumption characteristics. As resource providers,mobile devices can join and leave the distributed computing environment unpredictably. This interrupts the undergoing operation, and the delay or failure of completing the operation may cause a system failure. In this paper, we propose a monitoring technique based on Load Balancing.